The Effect of Abnormal Audit Fees, Key Audit Matters, and Audit Tenure on Audit Quality (A Study of Companies Listed on the Indonesia Stock Exchange for the 2022-2023 Period) - Dimas Hafizh Gunawan; Suryani, Elly (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
Audit quality refers to the auditor's ability to detect and disclose errors in financial documents. In performing this task, auditors are required to comply with applicable auditing standards and the professional code of ethics. This study aimed to examine the effect of abnormal audit fee, key audit matters, and audit tenure on audit quality in energy sector companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2023 period. The population in this study consisted of energy sector companies listed on the IDX during the specified period. The sampling method used was purposive sampling, resulting in 51 company-year observations over two years. After the removal of 7 companies identified as outliers, the final sample consisted of 44 companies. The study utilized secondary data and applied panel data regression using EViews 13, with firm size and audit firm size included as control variables. The results of the simultaneous test indicated that abnormal audit fee, key audit matters, and audit tenure had a significant effect on audit quality. However, the partial test showed that each of these variables individually did not have a statistically significant effect. These findings suggest that although the three variables are collectively important in influencing audit quality, none of them had a strong individual impact on audit quality in the energy sector during the observation period. This study offers important implications for regulators and companies in understanding and evaluating the broader factors that influence the quality of audit services in practice.